Phytochemical, Antimicrobial, Elemental and Anionic Analysis of Methanol Leaf Extract of Ziziphus mauritiana LAM (Bulletin of Pure and Applied Sciences-Chemistry, 2021)
Ziziphus mauritiana is used as a medicinal plants especially its fruit and leaf. In this work the leaf of Z.  Mauritiana was screened, investigated qualitatively for its Phytochemical constituent and  antimicrobial study carried out using disc diffusion method on some selected microorganisms. Elemental and anionic contents were carried out to determine the concentration levels of Zn, Pb, K,  SO42-, Cl- and PO43-. The result of the phytochemical screening of the methanol leaf extractof Z.  mauritiana revealed the presence of carbohydrates, tannins, saponins, cardiac glycoside and  flavonoids. While alkaloids, terpenoids and phlobatannins were absent. The antimicrobial study  revealed significant activity concentration-dependent at P